Competing for the future - Hamel, Gary.; Prahalad, C. K. (Boston, Mass. : Harvard Business School Press, 1994)
Annotation 0875847161.
Annotation With Competing for the Future, managers have seen how they can reshape their industries. Gary Hamel and C.K. Prahalad offer a masterful blueprint for what your company must be doing today if it is to occupy the competitive high ground of tomorrow. By showing that the key to future industry leadership is to develop an independent point of view about tomorrow's opportunities and build capabilities that exploit them, Hamel and Prahalad reveal an entirely new definition of what it means to be strategic - and successful.
Getting off the treadmill -- How competition for the future is different -- Learning to forget -- Competing for industry foresight -- Crafting strategic architecture -- Strategy as stretch -- Strategy as leverage -- Competing to shape the future -- Building gateways to the future -- Embedding the core competence perspective -- Securing the future -- Thinking differently.
Includes bibliographical references (pages 303-306) and index.
Print version record.
Keywords: Competition; Business planning; Competition, International; Concurrence; Projet d'entreprise.; Concurrence internationale; Entreprises -- Planification; Planification stratégique; BUSINESS & ECONOMICS -- Strategic Planning; Business planning; Competition; Competition, International; Concurrentie; Strategisch management; Internationale Wettbewerbsfähigkeit; Reorganisation; Unternehmen; Wettbewerbsstrategie; COMPETITION; BUSINESS MANAGEMENT; CORPORATE PLANNING; INTERNATIONAL COMPETITION; elektronické knihy; electronic books